Math City Map: Student Numeration Using Android-Based Technology Media - Pita Ilindia, Lis; Widyaningrum, Indah; Rahayu, Chika (Universitas Ma'arif Lampung, 2024)
Students' low numeracy skills impact students' learning outcomes and progress in mathematics. To improve these abilities, we can use operating system-based application learning media. The Math City Map application is a system that works on iOS/Android devices that helps students become actively involved and master the material being studied. This research aimed to see students' numeracy abilities after applying the Math City Map to statistics material. This research is research whose data uses quantitative, systematic, planned, and structured analysis. The design used in the study is an experimental Design with One Group Pre-test-Post-test Design. Tests, questionnaires, and documentation are data collection methods to assess students' numeracy skills. The results of the student test data stated that 82% of students could use numbers and symbols, 69% could analyze information, and 48% could use the analysis results to make decisions and formulate conclusions. By obtaining this percentage of students' numeracy abilities, it can be stated that using the Math City Map (MCM) application can train students to use symbols, numbers, tables, and diagrams to be more careful and thorough in analyzing information and determining answers to solve mathematical problems.